Transcendental Communication with Near Death Experience - Lorita Simamora, Santa; Sulthan Fadhilah, Muhammad; Andika, Dicky; Gunawan, M; Jamilah Mihardja, Eli (COMMICAST, 2024)
This study examines the experiences of individuals with Near-Death Experiences (NDEs) or individuals who have had near-death experiences. This phenomenon is still without a concrete definition and clear mechanism, almost like a mystery, as it is not perceived by others, only felt by the individuals who experience it. There are few individuals with near-death experiences due to severe illness or tragic accidents. The Near-Death Experience phenomenon falls into the category of unique and rare events, with a relatively small number of studies from the perspective of transcendental communication in Indonesia. The aim of this study is to understand and describe how individuals interpret their experiences of transcendental communication when in a coma or abnormal consciousness. This study uses a phenomenological approach with three subjects. The results of this study are expected to deeply explore the experiences of individuals' transcendental communication with their Creator during near-death conditions. These experiences serve as lessons for everyone that death will surely come, hence the need to prepare with good deeds and worship. To delve deeper into the description of the near-death transcendental communication experiences, in-depth interviews were conducted with subjects who voluntarily agreed to participate. The subjects were selected using purposive sampling techniques, specifically snowball sampling. The study results indicate that the transcendental communication experienced by the three subjects involved communicating with their God, their Creator, resulting in profound meanings for them. All three subjects perceived their near-death condition as a pivotal point for behavioral change towards a better direction in life.